(untitled) (Proceedings of Southern Federal University. Philology, 2020)
Silence is a communicative phenomenon with its own psychological meaning and evaluative semantics. The article treats silence, when it replaces speech, as a zero verbal reaction, the meaning of which depends on the specific communicative situation and on the previous phrase of the dialogue. The research of communicatively meaningful silence in the novel of Mikhail Sholokhov «And Quiet Flows the Don» suggests that it is closely connected with the cultural and ethnic norms of behavior that are common among Don Cossacks. Emotive silence that means a threat and evaluative silence as a reaction to the previous phrase of a dialogue are two of the typical ways to express the emotions of characters that Mikhail Sholokhov uses in his novel «And Quiet Flows the Don». The analysis of such dialogical fragments of the novel that represent communicative situations of conflict made it possible to single out several functions of silence that are typical of this text, and the actualization of these functions helps to express emotive-evaluative meanings. Primarily the expressive and the evaluative functions of silence help the text of the novel to depict a living communicative situation. Keywords: communication, silence, emotional state of a character. DOI 10.18522/1995-0640-2020-1-36-44